2011
DOI: 10.1093/bioinformatics/btr551
|View full text |Cite
|
Sign up to set email alerts
|

Neural fate decisions mediated by trans-activation and cis-inhibition in Notch signaling

Abstract: In this article, we present a computational model for neural fate decisions based on intertwined dynamics with trans-activation and cis-inhibition involving the Hes1, Notch and Dll1 proteins. In agreement with experimental observations, the model predicts that both trans-activation and cis-inhibition play critical roles in regulating the choice between remaining as a progenitor and embarking on neural differentiation. In particular, trans-activation is essential for generation of oscillations in neural progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 29 publications
1
44
1
Order By: Relevance
“…Our results confirmed that Notch-Delta alone allows only two states: Sender (S) or Receiver (R), which is consistent with previous studies (6,13,14,17). Our key findings are that due to the Delta-Jagged asymmetry, the Notch signaling through both Delta and Jagged gives rise to a hybrid Sender/Receiver (S/R) state in addition to Sender and Receiver states.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results confirmed that Notch-Delta alone allows only two states: Sender (S) or Receiver (R), which is consistent with previous studies (6,13,14,17). Our key findings are that due to the Delta-Jagged asymmetry, the Notch signaling through both Delta and Jagged gives rise to a hybrid Sender/Receiver (S/R) state in addition to Sender and Receiver states.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas Notch-Delta signaling has been extensively studied both theoretically and experimentally (6,(13)(14)(15)(16)(17) and is well understood, the role of Jagged in the Notch-Delta-Jagged signaling is still elusive. Here, we introduced a specially designed theoretical framework to study Notch signaling through both Delta and Jagged which incorporates the effect of the asymmetries between these two key ligands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mathematical models, critical thresholds for such transitions correspond to bifurcations [6]. Typical bifurcations are those that mark the transition from one stable equilibrium to another one through a saddle-node or a pitchfork bifurcation [7] or the transition from an oscillatory attractor to a stable equilibrium through a Hopf bifurcation [8].…”
Section: Introductionmentioning
confidence: 99%
“…These two levels of asymmetry in Notch-Delta vs. Notch-Jagged signaling call for elucidating their different operating principles. Much experimental and theoretical research efforts have been directed towards understanding the Notch-Delta-dependent cell fate determination [10,20,21,22,23,24]. In contrast, the role of Notch-Jagged signaling has gained limited research attention despite its crucial role during embryonic development, and promoting tumor progression in multiple ways.…”
Section: Introductionmentioning
confidence: 99%